2010
DOI: 10.1111/j.1747-0080.2010.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Today's profession: Views and practices of private practice dietitians re Medicare Chronic Disease Management program

Abstract: Aim:  To explore private practice dietitians' experiences of Medicare Chronic Disease Management allied health program operations, particularly regarding workplace environments, patient management practices and acceptance of the program. Methods:  A cross‐sectional national survey was administered electronically in 2008. All private practice members of Dietitians Association of Australia were invited to participate. A 38‐item questionnaire asked about referrals, patients, fees, billing and participant demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…No significant differences in the time dietitians spent on initial and review consultations were found in the present study. Dietitians have previously reported that due to the counselling nature of dietetics, half hour initial consultations are insufficient to provide adequate care . However, dietitians consider the time frame covered by Medicare (20 minutes) adequate for review consultations .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant differences in the time dietitians spent on initial and review consultations were found in the present study. Dietitians have previously reported that due to the counselling nature of dietetics, half hour initial consultations are insufficient to provide adequate care . However, dietitians consider the time frame covered by Medicare (20 minutes) adequate for review consultations .…”
Section: Discussionmentioning
confidence: 99%
“…Dietitians have previously reported that due to the counselling nature of dietetics, half hour initial consultations are insufficient to provide adequate care . However, dietitians consider the time frame covered by Medicare (20 minutes) adequate for review consultations . Therefore, it appears more financially sustainable for dietitians to retain patients through review consultations, rather than conducting numerous initial consultations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2007 study of dietitian CDM providers found that type 2 diabetes mellitus, obesity and cardiac conditions were regarded as the most commonly referred diagnosis types for Medicarereferred dietetics patients. 16 Furthermore, the number of CDM services provided to patients per each Medicare provider by dietetics and by diabetes education in 2008-09 were among the highest of all providers, 9 suggesting that patients with type 2 diabetes were receiving these education services. Indications are that patients who require the Medicare services for chronic conditions may be receiving them.…”
Section: Utilisation Of Allied Health Providers By Profession and By mentioning
confidence: 99%
“…Under existing MBS funding, patients with chronic conditions (including patients with obesity who have co-morbidities or multiple risk factors) are eligible for a GP Management Plan (GPMP), which includes five subsidised allied health visits. However, these five visits are often insufficient to meet all the care needs of patients and to provide care consistent with best-practice guidelines; for example, weight management guidelines produced by the Dietitians Association of Australia (Cant 2010). This is particularly the case for patients with obesity and complex comorbidities who require care across multiple allied health specialties.…”
Section: Discussionmentioning
confidence: 99%